Acceptability of Hormonal Contraceptives as a Smoking Cessation Aid for Women of Reproductive Age: A Web-Based Cross-Sectional Survey - Samantha J. Werts-Pelter; Briana M. Choi; Stephanie Mallahan; Nicole Person-Rennell; Alicia Allen (Women's Health Reports)
Introduction: Cigarette smoking is the most common cause of preventable cancers and other premature morbidity and mortality. Modifying hormonal patterns using hormonal contraceptives (HCs) may lead to improved smoking cessation outcomes in women, though the acceptability of this is unknown. Therefore, we explored the willingness of reproductive-age women who smoke to use HC for cessation. Methods: A cross-sectional online survey was conducted with a convenience sample of reproductive-age women living in the United States who self-reported smoking combustible cigarettes. Questions covered smoking history, previous HC use, and willingness to use various HC methods (i.e., injectable, oral, patch, vaginal insert) for cessation. Chi-squared tests and logistic regression were conducted using StataBE 17.1. Results: Of 358 eligible respondents, n = 312 (86.9%) reported previous HC use. Average age of those with HC use history was 32.1 ± 6.1 years compared with 27.8 ± 6.7 years for those without history of HC use (p = 0.001). Of respondents who reported previous HC use, 75.6% reported willingness to use HCs, compared with 60.9% of those without a history of HC use. Overall, willingness to use various types of HC ranged from 22.6% for the vaginal insert to 59.2% willing to use an oral contraceptive. Discussion: These observations indicate that most women who smoke cigarettes are willing to use HC for a smoking cessation aid, especially if they have a history of HC use and with an oral form of HC. To improve the rate of smoking cessation for women of reproductive age, future interventions should explore how to incorporate HC for cessation.